Application of Natural Organic Residues as Adsorbents to Remove Lead from Waters - Oliveira, Luciana C.; Botero, Wander G.; Farias, Tamyris S.; Santos, Josué C. C.; Gabriel, Gabriele V. M.; Goveia, Danielle [UNESP]; Cacuro, Thiago A.; Waldman, Walter R. (Springer Nature, 2019)
The contamination of the environment by potentially toxic metals is highlighted by possible impacts of their high availability. Thus, the development of alternative absorbents that can be used in the remediation of contaminated areas, systems that are able to interact with these metals and affect their disposal, transportation, and bioavailability, is of great interest. Natural organic residue (NOR), often discarded as waste, is a promising alternative because it is capable of affecting the bioavailability of potentially toxic metals in the environment. This study assessed the interaction between NOR and NOR ashes (inorganic constituents) and lead ion (Pb2+), and its potential of adsorption, in order to analyze their use in contaminated areas. Two different NOR were evaluated and its structural characteristics presented differences in their organic material content and in its complexing capacity. NOR2 presented better capacity of complexing and adsorption of Pb2+ ions, performance that must be associated to the higher amount of organic matter present in the soil of this residue. In addition, the adsorption at pH 7.0 occurred through specific interactions with certain functional groups on the surface of NOR and NOR ashes. Besides that, the retention capacity of the Pb2+ ions was concentration dependent, in which the highest amount of mass will be the adsorbent retention. In light of this, the results obtained in this work highlight the importance of natural organic residues as a natural adsorbent material to lead removal.
Keywords: Adsorption of lead; Environmental contamination; Humic substances; NOR complexing capacity; Remediation